General solution growth of mesoporous NiCo2O4 nanosheets on various conductive substrates as high-performance electrodes for supercapacitors - Lou, David Xiong Wen (2014)
Mesoporous NiCo2O4 nanosheets can be directly grown on various conductive substrates, such as Ni foam, Ti foil, stainless-steel foil and flexible graphite paper, through a general template-free solution method combined with a simple post annealing treatment. As a highly integrated binder- and conductive-agent-free electrode for supercapacitors, the mesoporous NiCo2O4 nanosheets supported on Ni foam deliver ultrahigh capacitance and excellent high-rate cycling stability.